Surface modified zinc oxide particles, dispersions, cosmetics

By attaching an alkoxysilane coupling agent to the surface-modified zinc oxide particles and controlling the particle size, the problem of poor dispersion in oily cosmetics is solved, and high transparency and excellent ultraviolet shielding are achieved.

CN115485241BActive Publication Date: 2025-03-25SUMITOMO OSAKA CEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080100250.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-30
Publication Date
2025-03-25
Estimated Expiration
2040-04-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively disperse surface modified zinc oxide particles in oily cosmetics, resulting in insufficient transparency and ultraviolet shielding.

Method used

By attaching a silane coupling agent with an alkoxy group to the surface-modified zinc oxide particles, and measuring the particle size d50 to 4 μm or less by a laser diffraction/scattering particle size distribution measuring device, surface-modified zinc oxide particles that are easily dispersed were prepared.

Benefits of technology

The modified zinc oxide particles are dispersed with less energy in oily cosmetics, significantly improving transparency and UV shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115485241B_ABST
    Figure CN115485241B_ABST
Patent Text Reader

Abstract

A surface-modified zinc oxide particle having a silane coupling agent on the surface, the silane coupling agent having an alkoxy group, and a d50 of 4 μm or less when measured by the following measuring method using a laser diffraction / scattering particle size distribution measuring device. (Measuring method) 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane and 2 g of polyglycerol-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane are mixed to obtain a mixed solution, a homogenizer is used to disperse the obtained mixed solution for 5 minutes at 9500 rpm to obtain a dispersion solution, a measuring solution diluted with cyclopentasiloxane to obtain a content of surface-modified zinc oxide particles in the obtained dispersion solution of 0.01 mass % is prepared, and the obtained measuring solution is used to measure d50 using a laser diffraction / scattering particle size distribution measuring device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to surface modified zinc oxide particles, dispersion liquid and cosmetic material. Background Art

[0002] It is known that zinc oxide has excellent ultraviolet shielding ability, high gas barrier properties and high transparency. Therefore, particles formed of zinc oxide (hereinafter referred to as "zinc oxide particles") are used as a forming material for various raw materials that have functions such as ultraviolet shielding or gas barrier and require transparency. Examples of such raw materials include ultraviolet shielding films, ultraviolet shielding glass, cosmetics, gas barrier films, and the like.

[0003] As a method for making the above-mentioned various raw materials transparent, for example, a method of reducing the primary particle size of zinc oxide particles as a forming material can be cited. As a method for reducing the primary particle size of zinc oxide particles, various methods such as thermal decomposition method and gas phase method have been studied (for example, refer to Patent Documents 1 and 2).

[0004] When zinc oxide particles are applied to cosmetics, surface treatment of the zinc oxide particles is performed in order to make the surface of the zinc oxide particles match the properties of the cosmetics or to suppress the catalytic activity of the zinc oxide particles.

[0005] When zinc oxide particles are incorporated into oily cosmetics or emulsion oil phases, zinc oxide particles having alkoxy groups on the surface are used after surface treatment with a silane coupling agent having an alkoxy group or the like (see, for example, Patent Documents 3 and 4).

[0006] In the following description, zinc oxide particles having a silane coupling agent on the surface are referred to as surface-modified zinc oxide particles.

[0007] The surface-modified zinc oxide particles are directly blended into cosmetics, or in the form of a dispersion dispersed in a dispersion medium.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2002-284527

[0011] Patent Document 2: Japanese Patent Application Publication No. 2000-95519

[0012] Patent Document 3: International Publication No. 2017 / 130632

[0013] Patent Document 4: Japanese Patent Application Publication No. 2007-51188 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] However, even zinc oxide particles having a silane coupling agent on the surface require a large amount of dispersibility in order to be blended into an oily cosmetic, and even if blended into an oily cosmetic, sufficient transparency and ultraviolet shielding properties cannot be obtained.

[0016] The present invention has been made in view of the above circumstances, and its object is to provide a surface-modified zinc oxide particle which can be easily blended into an oily cosmetic and has excellent transparency and ultraviolet shielding properties. Another object is to provide a dispersion liquid and a cosmetic containing such surface-modified zinc oxide particles.

[0017] Solutions for solving problems

[0018] In order to solve the above-mentioned problems, a first aspect of the present invention provides a surface-modified zinc oxide particle having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group, and the surface-modified zinc oxide particle is characterized in that the particle diameter d50 at which the cumulative volume percentage of the particle size distribution is 50% when measured by the following measurement method using a laser diffraction / scattering particle size distribution analyzer is 4 μm or less.

[0019] (Measurement method)

[0020] 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane, and 2 g of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane were mixed to obtain a mixed solution, and the obtained mixed solution was dispersed at 9500 rpm for 5 minutes using a homogenizer to obtain a dispersion solution. A measurement solution was prepared by diluting the obtained dispersion solution with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles in the obtained dispersion solution became 0.01% by mass. Using the obtained measurement solution, d50 was measured using a laser diffraction / scattering particle size distribution analyzer.

[0021] In the first aspect of the present invention, the surface-modified zinc oxide particles may be constituted as follows: * a * b * b in the chromaticity diagram of the color system * It is 4.0 or more and 18 or less.

[0022] In the first aspect of the present invention, the silane coupling agent may be at least one selected from the group consisting of alkylalkoxysilane, allylalkoxysilane, polysiloxane having an alkyl group in a side chain, and polysiloxane having an allyl group in a side chain.

[0023] In the first aspect of the present invention, the silane coupling agent may be at least one selected from the group consisting of octyltriethoxysilane, octyltrimethoxysilane, and a dimethoxydiphenylsilane-triethoxyoctanoylsilane crosslinked polymer.

[0024] In order to solve the above-mentioned problems, a second aspect of the present invention provides a dispersion liquid containing the above-mentioned surface-modified zinc oxide particles and a dispersion medium.

[0025] In order to solve the above-mentioned problems, a third aspect of the present invention provides a cosmetic comprising at least one selected from the group consisting of the above-mentioned surface-modified zinc oxide particles and the above-mentioned dispersion.

[0026] In order to solve the above-mentioned problems, a fourth aspect of the present invention provides a method for selecting surface-modified zinc oxide particles, which is the method for selecting the surface-modified zinc oxide particles. The method of the fourth aspect is as follows: surface-modified zinc oxide particles having a silane coupling agent on the surface, the silane coupling agent having an alkoxy group, 10 g of the surface-modified zinc oxide particles, 88 g of cyclopentasiloxane, and 2 g of polyglycerol-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane are mixed to obtain a mixed solution, the obtained mixed solution is dispersed at 9500 rpm for 5 minutes using a homogenizer to obtain a dispersion solution, a measurement solution is prepared which is diluted with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles in the obtained dispersion solution becomes 0.01 mass%, and the particle size d50 when the cumulative volume percentage of the particle size distribution is 50% is measured using a laser diffraction / scattering particle size distribution measuring device using the obtained measurement solution, and it is determined whether the d50 is 4 μm or less. If the d50 is 4 μm or less, the surface-modified zinc oxide particles are selected.

[0027] In order to solve the above-mentioned problems, a fifth aspect of the present invention provides a method for producing surface-modified zinc oxide particles, which is the method for producing the above-mentioned surface-modified zinc oxide particles.

[0028] The method of the fifth embodiment is the following method: comprising: a step of placing a silane coupling agent having an alkoxy group, a solvent and zinc oxide particles into a disperser to prepare a mixed solution; and a step of dispersing the mixed solution using the disperser to obtain surface-modified zinc oxide particles having a d50 of 4 μm or less, wherein in the step of preparing the mixed solution, the content of the solvent in the mixed solution is 40 mass % or more and 95 mass % or less.

[0029] Effects of the Invention

[0030] According to the present invention, it is possible to provide surface-modified zinc oxide particles which can be dispersed in cosmetics with less energy and have excellent transparency and ultraviolet shielding properties. In addition, according to the present invention, it is possible to provide a dispersion liquid and a cosmetic containing such surface-modified zinc oxide particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a figure which shows the dispersion state of the surface-modified zinc oxide particles of Example 4 (right) and Comparative Example 2 (left). DETAILED DESCRIPTION

[0032] An embodiment of the method for producing the surface-modified zinc oxide particles of the present invention will be described.

[0033] In addition, in the present embodiment, specific description is given for better understanding of the purpose of the invention, and unless otherwise specified, the present invention is not limited. The present invention may change, omit, replace, add, etc. to numerical values, amounts, materials, types, time, temperature, sequence, etc. within the scope of the purpose.

[0034] [Surface modified zinc oxide particles]

[0035] The surface-modified zinc oxide particles of the present embodiment are surface-modified zinc oxide particles having a silane coupling agent on the surface, the silane coupling agent having an alkoxy group, and the particle size d50 of the particles when the cumulative volume percentage of the particle size distribution is 50% when measured by the following measurement method using a laser diffraction / scattering particle size distribution measuring device is 4 μm or less.

[0036] (Measurement method)

[0037] 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane, and 2 g of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane were mixed to obtain a mixed solution, and the obtained mixed solution was dispersed at 9500 rpm for 5 minutes using a homogenizer to obtain a dispersion solution. A measurement solution was prepared by diluting the obtained dispersion solution with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles in the obtained dispersion solution became 0.01% by mass. Using the obtained measurement solution, d50 was measured using a laser diffraction / scattering particle size distribution analyzer.

[0038] Here, as cyclopentasiloxane, DOWSIL SH245 Fluid manufactured by Dow Toray Industries, Ltd. can be used, and as polyglyceryl-3 polydimethylsilyl hydroxyethyl dimethicone, KF-6106 manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0039] Cyclopentasiloxane is a solvent commonly used in oily cosmetics. Therefore, if the surface-modified zinc oxide particles are easily dispersed in cyclopentasiloxane, it can be judged that they are easily dispersed in oily cosmetics. Therefore, cyclopentasiloxane was used as an evaluation solvent.

[0040] Polyglyceryl-3 polydimethylsilyl hydroxyethyl dimethicone is a dispersant commonly used in oily cosmetics. Therefore, if 2 g (2% by mass) of this dispersant is easily dispersed in cyclopentasiloxane, it can be judged that it is easily dispersed in oily cosmetics.

[0041] Here, "easy to disperse" means that a dispersion liquid having a small dispersed particle size can be obtained with weak dispersion energy. Surface-modified zinc oxide particles having a small dispersed particle size are excellent in transparency and ultraviolet shielding properties when blended into cosmetics.

[0042] The reason for setting the surface-modified zinc oxide particles to 10 g (10% by mass) in the evaluation is that if the content of the surface-modified zinc oxide particles in the dispersion is 10% by mass, it is an appropriate amount sufficient to evaluate the dispersibility. That is, if the content of the surface-modified zinc oxide particles in the dispersion is less than 10% by mass, the amount of the dispersed surface-modified zinc oxide particles is too small, and it is sometimes difficult to distinguish the difference. On the other hand, even if the content of the surface-modified zinc oxide particles is set to an amount exceeding 10% by mass, it is impossible to perform an appropriate evaluation due to the excessive content, or the tendency of the dispersibility will not change, so there is no advantage of setting the amount to more than 10% by mass.

[0043] The condition of 9500 rpm of the homogenizer is relatively weak as a force for dispersing the powder. Therefore, if the dispersed particle size is small when the surface-modified zinc oxide particles are dispersed at this level of force, it can be evaluated that the dispersibility is excellent.

[0044] The reason for setting the dispersion treatment time to 5 minutes is that the surface-modified zinc oxide particles with a large dispersion particle size when dispersed for 5 minutes using a homogenizer at 9500 rpm can be evaluated as not excellent in dispersibility. As a homogenizer, a general stirring homogenizer that can be used for the dispersion of particles can be used. If specific examples are cited, for example, homogenizers such as T25basic (IKA company system) of ULTRA-TURRAX (registered trademark) series can be preferably used.

[0045] The surface-modified zinc oxide particles of the present embodiment are surface-modified zinc oxide particles having a silane coupling agent having an alkoxy group on the surface. That is, the surface-modified zinc oxide particles of the present embodiment are zinc oxide particles having a silane coupling agent having an alkoxy group attached to at least a portion of the surface.

[0046] The specific surface area of ​​the surface-modified zinc oxide particles of this embodiment can be arbitrarily selected, but is preferably 1.5 m 2 / g or more, more preferably 2.5m 2 / g or more, more preferably 4m 2 / g or more. In addition, the specific surface area of ​​the surface-modified zinc oxide particles can be, for example, 55 m 2 / g or less, preferably 50m 2 / g or less, more preferably 45m 2 If necessary, the specific surface area of ​​the surface-modified zinc oxide particles may be 40 m 2 / g or less, and can also be 30m 2 / g or less, and can also be 10m2 The above upper limit value and lower limit value of the specific surface area of ​​the surface-modified zinc oxide particles may be arbitrarily combined.

[0047] If the specific surface area of ​​the surface-modified zinc oxide particles is 1.5 m 2 / g or more and 50m 2 / g or less, the transparency and ultraviolet shielding properties when blended into cosmetics are excellent.

[0048] In order to improve the transparency when blended into cosmetics, the specific surface area of ​​the surface-modified zinc oxide particles is preferably 8 m 2 / g or more, more preferably 15m 2 / g or more, more preferably 20m 2 / g or above.

[0049] For example, the specific surface area of ​​surface-modified zinc oxide particles is 20 m 2 / g or more and 50m 2 / g or less, preferably 20m 2 / g or more and 48m 2 / g or less, more preferably 20m 2 / g or more and 46m 2 / g or less. It can also be 20.0m 2 / g or more and 30.0m 2 / g or less, 20.0m 2 / g or above and 38.0m 2 / g or less or 20.0m 2 / g or above and 44.0m 2 / g or less.

[0050] By making the specific surface area of ​​the surface-modified zinc oxide particles 20 m 2 / g or more, when blended into oily cosmetics containing silicone oil or the like, cosmetics with excellent transparency can be obtained. On the other hand, by making the specific surface area of ​​the surface-modified zinc oxide particles 50m 2 / g or less, the surface energy of the particles will not be too large, and thus the particles can be blended into oily cosmetics (hereinafter, sometimes simply referred to as "cosmetics") with less energy.

[0051] On the other hand, in order to increase the UVA-band shielding property when blended into cosmetics, the specific surface area of ​​the surface-modified zinc oxide particles is preferably less than 20 m 2 / g, more preferably 15m 2 / g or less, more preferably 8m 2 / g or less.

[0052] For example, the specific surface area of ​​the surface-modified zinc oxide particles is preferably 1.5 m2 / g or more and less than 20m 2 / g, more preferably 1.5m 2 / g or more and 15m 2 / g or less, more preferably 1.5m 2 / g or more and 8m 2 / g or less.

[0053] By making the specific surface area of ​​the surface-modified zinc oxide particles 1.5 m 2 / g or more, when blended into oily cosmetics containing silicone oil or the like, a transparent cosmetic can be obtained. On the other hand, by making the specific surface area of ​​the surface-modified zinc oxide particles less than 20 m 2 / g, the surface energy of the particles is not too large, and thus the particles can be blended into oily cosmetics with less energy, and cosmetics having excellent ultraviolet shielding properties in the UVA region can be obtained.

[0054] The specific surface area (unit: m 2 / g) is the BET specific surface area obtained by the BET method.

[0055] As a method for measuring the specific surface area of ​​the surface-modified zinc oxide particles, for example, there is a BET method using a fully automatic specific surface area measuring apparatus (trade name: Macsorb HM Model-1201, manufactured by MOUNTECH Corporation).

[0056] The particle size (d50) of the surface-modified zinc oxide particles of the present embodiment when the cumulative volume percentage of the particle size distribution in the above-mentioned measuring method is 50% (hereinafter, sometimes simply referred to as "d50") is preferably 4.00 μm or less, more preferably 1.00 μm or less, further preferably 0.60 μm or less, and particularly preferably 0.40 μm or less. These values ​​may also be 2.00 μm or less, 0.50 μm or less, 0.30 μm or less, 0.20 μm or less, 0.10 μm or less, or 0.08 μm or less, as required.

[0057] The smaller the d50, the better, but it cannot be less than the primary particle size of the surface-modified zinc oxide particles. Therefore, the lower limit of d50 can be 0.02 μm, 0.05 μm, or 0.10 μm. As required, the lower limit can also be 0.03 μm, 0.06 μm, or 0.08 μm.

[0058] In addition, the primary particle size can be obtained by observing the surface-modified zinc oxide particles (for example, 100 particles) using a transmission electron microscope, etc. to obtain the maximum diameter (maximum major axis) of each particle, and set it as the average value of these values. The primary particle size of the surface-modified zinc oxide particles can be arbitrarily selected, for example, it can be 21nm to 713nm. If the transparency when mixed into cosmetics is to be improved, it is preferably 22nm to 54nm, and more preferably 23nm to 54nm. If the ultraviolet shielding property in the UVA region when mixed into cosmetics is to be increased, it is preferably 54nm to 713nm, more preferably 71nm to 713nm, and further preferably 134nm to 713nm. However, it is not limited to these examples.

[0059] In the measurement method of the present embodiment, a laser diffraction / scattering particle size distribution measuring apparatus, model LA-920 manufactured by Horiba, Ltd., is used, but the present invention is not limited thereto, and a known apparatus may be used.

[0060] Hereinafter, the reason why the surface-modified zinc oxide particles having d50 of 4 μm or less can be dispersed in an oily cosmetic with less energy and have excellent ultraviolet shielding properties in the evaluation by the above-mentioned measuring method will be described.

[0061] The present inventors have found that when zinc oxide particles are surface-treated with a silane coupling agent having an alkoxy group (hereinafter, sometimes referred to as a "silane coupling agent"), the zinc oxide particles and the silane coupling agent are dispersed with high energy using a disperser having a large dispersion energy such as a bead mill, and as a result, excellent surface-modified zinc oxide particles that can be easily dispersed in a silicone-containing cosmetic can be obtained. Here, the above-mentioned dispersion energy refers to the energy required to disperse the zinc oxide particles in a solvent using the silane coupling agent. In other words, it refers to the energy to the extent that the agglomerated zinc oxide particles are disintegrated.

[0062] The details of this mechanism are presumed to be as follows.

[0063] The specific surface area is 1.5m 2 / g or more and 50m 2 Zinc oxide particles with a specific surface area of ​​20 m 2 / g or more and 50m 2 / g or less zinc oxide particles are more likely to condense with each other. Therefore, in the past, a surface treatment was performed using a silane coupling agent in a condensed state. However, if such particles that have been surface-treated in a state where the particles are condensed with each other are mixed with the oil component of an oily cosmetic, the particles are dispersed while maintaining the condensed state. Therefore, the transparency and ultraviolet shielding properties are deteriorated due to the condensation. In order to prevent the deterioration as described above, it is necessary to dismantle the condensation of the particles, so that more dispersion energy is required when making an oily cosmetic. However, even if the transparency and ultraviolet shielding properties are improved by dismantling the condensation with high energy, the surface treatment state of the surface of the dismantled zinc oxide particles is not uniform because the condensation of the surface-treated condensate is dismantled while maintaining the condensed state. As a result, the dispersion stability of the surface-modified zinc oxide particles in the oily cosmetic is impaired.

[0064] However, by dispersing the zinc oxide particles in a solvent at high energy, the surface treatment can be performed with a silane coupling agent in a state where the aggregation of the zinc oxide particles is broken up, and it is presumed that the silane coupling agent can be substantially uniformly present on the entire surface of the zinc oxide particles. Therefore, if the surface-modified zinc oxide particles in this state are mixed with an oil component, the compatibility of all parts of the surface of the zinc oxide particles with the oil component is good, and the particles can be dispersed in the oil component at low energy. In addition, the silane coupling agent is substantially uniformly present on the surface of the zinc oxide particles, so it is presumed that a cosmetic material can be obtained in which the aggregation of the surface-modified zinc oxide particles is also suppressed and which has excellent transparency, ultraviolet shielding properties, and dispersion stability.

[0065] However, it is very difficult to directly confirm that the silane coupling agent is uniformly present on the surface of the zinc oxide particles. In the present embodiment, it is presumed that the effect of being able to easily disperse the surface-modified zinc oxide particles in the solvent is manifested by a complex linkage of multiple factors, specifically, by a complex linkage of multiple factors such as the shape of the zinc oxide particles, the specific surface area, the particle size distribution, the degree of hydrolysis of the silane coupling agent having an alkoxy group, the degree of attachment of the silane coupling agent having an alkoxy group to the zinc oxide particles, or the attachment rate of the silane coupling agent having an alkoxy group on the zinc oxide particles. Therefore, it is considered almost impossible to directly determine the characteristics of the surface-modified zinc oxide particles of the present embodiment based on the state of the surface of the zinc oxide particles surface-modified by the silane coupling agent having an alkoxy group.

[0066] Therefore, as a result of various studies conducted by the present inventors, it was found that by treating the surface of zinc oxide particles with a silane coupling agent at high energy using the above-mentioned measuring method until d50 becomes 4 μm or less (i.e., to achieve the target dispersibility), surface-modified zinc oxide particles that are easily dispersed in oily cosmetics and have excellent ultraviolet shielding properties can be obtained. In other words, the d50 value obtained by the above-mentioned measuring method can be considered as an indicator of whether the silane coupling agent is uniformly present on the surface of the zinc oxide particles.

[0067] In the present embodiment, surface-modified zinc oxide particles preferably used in cosmetics are used, and therefore zinc oxide particles are used as particles, a silane coupling agent having an alkoxy group is used as a surface-modifying material, cyclopentasiloxane is used as a dispersion medium, and polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane is used as a dispersant as an indicator for evaluating the state of surface treatment.

[0068] However, the evaluation method of the surface treatment state of the present embodiment is not limited to the combination of zinc oxide particles and a silane coupling agent having an alkoxy group, and can also be extended to particles and surface modification materials. That is, a dispersion medium to be used for dispersion is selected, and a dispersant is used for dispersion as required. In addition, the particles surface-modified by the surface modifier are dispersed in the dispersion medium with weak dispersion energy to measure the size of the dispersed particle size of the dispersion liquid as an indicator of the uniformity of the surface treatment.

[0069] When the surface treatment with a silane coupling agent is performed at high energy, the L of the surface-modified zinc oxide particles increases as the surface treatment progresses. * a * b * b in the chromaticity diagram of the color system * (hereinafter, sometimes referred to as "b * ”.) is larger than the b of zinc oxide particles before surface treatment. * Therefore, the surface modified zinc oxide particles b * It serves as an indicator of surface treatment with a silane coupling agent.

[0070] The surface modified zinc oxide particles of this embodiment have * It is preferably 4.0 to 18, more preferably 4.5 to 16. It may be 4.0 to 12, 4.5 to 11, or 5.0 to 10.0, etc., as required. * The difference may be, for example, 0.5 to 8.0, 1.0 to 8.0, 2.0 to 8.0, or 3.0 to 7.5, but is not limited to these values.

[0071] As the b of the surface modified zinc oxide particles* The method can utilize a known method such as using a spectrocolorimeter, and for example, a spectrocolorimeter (Spectro Color Meter SE7700 manufactured by Nippon Denshoku Industries Co., Ltd.) can be used.

[0072] In this embodiment, "having a silane coupling agent on the surface" means that the silane coupling agent and the zinc oxide particles are in contact or bonded by the interaction therebetween. As contact, for example, physical adsorption can be cited. And as bonding, for example, ionic bonding, hydrogen bonding, covalent bonding, etc. can be cited.

[0073] The amount of the silane coupling agent in the surface-modified zinc oxide particles can be appropriately adjusted for use according to the specific surface area of ​​the zinc oxide particles and the hydrophobicity of the oily cosmetics to be blended. For example, the amount of the silane coupling agent in the surface-modified zinc oxide particles is preferably 1% by mass or more and 20% by mass or less relative to the zinc oxide particles, more preferably 2% by mass or more and 18% by mass or less, and further preferably 3% by mass or more and 16% by mass or less. As required, it can also be 3% by mass or more and 8% by mass or more and 5% by mass or more and 10% by mass or less. However, it is not limited to the examples described above.

[0074] The amount of the silane coupling agent in the surface-modified zinc oxide particles can be calculated by, for example, quantitatively analyzing the amount of Si in the surface-modified zinc oxide particles using an inductively coupled plasma emission spectrometer.

[0075] "Zinc Oxide Particles"

[0076] The specific surface area of ​​the zinc oxide particles (before surface treatment) of this embodiment can be arbitrarily selected, but is preferably 1.5 m 2 / g or more, more preferably 2.5m 2 / g or more, more preferably 4m 2 / g or more. In addition, the specific surface area of ​​the zinc oxide particles is preferably 50 m 2 / g or less, more preferably 45m 2 If necessary, the specific surface area of ​​the zinc oxide particles may be 40 m 2 / g or less, and can also be 30m 2 / g or less, and can also be 10m 2 / g or less.

[0077] The specific surface area of ​​the zinc oxide particles before the surface treatment and the specific surface area of ​​the surface-modified zinc oxide particles are slightly different depending on the attachment method of the silane coupling agent, but the change is not large.

[0078] Therefore, in order to obtain surface-modified zinc oxide particles having a desired specific surface area, zinc oxide particles having the desired specific surface area may be used. That is, the surface-modified zinc oxide particles of the present embodiment may preferably have the same value or range as the preferred specific surface area of ​​the zinc oxide particles described above.

[0079] L of zinc oxide particles before treatment * a * b * b in the chromaticity diagram of the color system * Preferably, it is 10 or less. * For zinc oxide particles within the above range, the surface modified zinc oxide particles have a b * The above range (i.e., 4.0 or more and 18 or less) can also be achieved, and the b of the surface-modified zinc oxide particles * Greater than the b of zinc oxide particles before surface treatment * As a result, the yellowness can be suppressed to a level suitable for cosmetics. * The lower limit of is not particularly limited, and may be 0, 1.0, or 1.5.

[0080] "Silane coupling agent having an alkoxy group"

[0081] The silane coupling agent having an alkoxy group may be arbitrarily selected, and preferably, among the silane coupling agents represented by the following general formula (1), silane coupling agents that can be used in cosmetics are used.

[0082] R 1 Si(OR 2 ) 3 (1)

[0083] (R 1 represents an alkyl group, a fluoroalkyl group or a phenyl group having 1 to 18 carbon atoms, and R 2 represents an alkyl group having 1 to 4 carbon atoms. )

[0084] As such a silane coupling agent, at least one selected from the group consisting of alkylalkoxysilane, allylalkoxysilane, polysiloxane having an alkyl group in a side chain, and polysiloxane having an allyl group in a side chain is preferred.

[0085] Examples of the alkylalkoxysilane include methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, ethyltributoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-propyltripropoxysilane, n-propyltributoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, isopropyltripropoxysilane, isopropyltributoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltripropoxysilane, phenyltributoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane (triethoxyoctanoylsilane), and n-octadecyltrimethoxysilane.

[0086] As the silane coupling agent, for example, a polymer-type silane coupling agent having a siloxane skeleton as the main chain and having an alkoxy group and an acrylic group in the molecular structure, such as dimethoxydiphenylsilane-triethoxycaprylylsilane crosslinked polymer, triethoxysilylethyl polydimethylsilylhydroxyethyl polydimethylsiloxane, and triethoxysilylethyl polydimethylsiloxyethylhexyl polydimethylsiloxane, can be used.

[0087] As the silane coupling agent, for example, fluoroalkylalkoxysilane such as trifluoropropyltrimethoxysilane, perfluorooctyltriethoxysilane, and tridecafluorooctyltriethoxysilane may be used.

[0088] These silane coupling agents may be used alone or in combination of two or more.

[0089] Among the above-mentioned silane coupling agents, silane coupling agents having an octyl group in the molecule are more preferred. Specifically, silane coupling agents that can cope with a wide range of polar oil phases from natural oils or ester oils to silicone oils are more preferred. As such a silane coupling agent, at least one selected from the group consisting of n-octyltriethoxysilane, n-octyltrimethoxysilane, and dimethoxydiphenylsilane-triethoxyoctanoylsilane crosslinked polymers is particularly preferred.

[0090] These silane coupling agents may be used alone or in combination of two or more.

[0091] In the surface-modified zinc oxide particles of the present embodiment, the zinc oxide particles may be surface-treated with a treatment agent other than the silane coupling agent, which is a surface treatment agent used in cosmetics, in addition to the silane coupling agent, within a range that does not inhibit the properties of the surface-modified zinc oxide particles.

[0092] Examples of the surface treatment agent other than the silane coupling agent include inorganic materials such as silica and alumina, and organic materials such as silicone compounds, fatty acids, fatty acid soaps, fatty acid esters, and organic titanate compounds.

[0093] "Method for producing surface-modified zinc oxide particles"

[0094] The method for producing surface-modified zinc oxide particles of the present embodiment includes: placing a silane coupling agent having an alkoxy group, a solvent, and zinc oxide particles in a disperser to prepare a mixed solution; and dispersing the mixed solution at a predetermined energy or higher.

[0095] The step of preparing the mixed solution may further contain water.

[0096] The step of preparing the mixed solution may further contain a catalyst.

[0097] A heating step may be performed after the above-mentioned dispersion treatment step.

[0098] The drying step may be performed after the above-mentioned dispersion treatment step or after the heating step.

[0099] The crushing treatment may be performed after the heating step or after the drying step.

[0100] The silane coupling agent having an alkoxy group and the zinc oxide particles used in the production method can be exactly the same as those described above, and therefore, description thereof will be omitted.

[0101] “Mixed liquid preparation process”

[0102] In the process of preparing the mixed solution, a silane coupling agent, a solvent and zinc oxide particles are placed in a disperser. Furthermore, pure water or a catalyst may be added as needed. These materials may be placed at the same time or sequentially. The order in which these materials are placed is not particularly limited. After being placed in the disperser, the mixture may be kept in its original state without stirring, or may be simply stirred. Furthermore, these materials may be mixed in advance before being placed in the dispersion and then placed in the disperser.

[0103] "Solvent"

[0104] The solvent is not particularly limited as long as it is a solvent that can be mixed with the silane coupling agent. As the solvent, for example, alcohols such as methanol, ethanol, n-propanol, isopropanol, and n-butanol, esters such as ethyl acetate and butyl acetate, or n-hexane, toluene, and xylene can be cited. Among these solvents, alcohols are preferred from the viewpoint of being miscible with water, and isopropanol is particularly preferred among the alcohols.

[0105] The content of the solvent in the mixed solution can be arbitrarily selected, but is preferably 40% by mass or more in order to suppress aggregation of zinc oxide particles. The upper limit of the content of the solvent is not particularly limited, but is preferably 95% by mass or less from the viewpoint of production efficiency.

[0106] The content of the zinc oxide particles in the mixed solution can be arbitrarily selected, but from the viewpoint of both suppressing the aggregation of the zinc oxide particles and production efficiency, it is preferably 1% by mass or more and 55% by mass or less, and more preferably 10% by mass or more and 50% by mass or less. The content may also be 15% by mass or more and 45% by mass or less, 20% by mass or more and 40% by mass or less, or 25% by mass or more and 35% by mass or less.

[0107] The content of the silane coupling agent in the mixed solution can be arbitrarily selected, as long as it is appropriately adjusted to impart the desired hydrophobicity to the zinc oxide particles. For example, the amount of the silane coupling agent in the surface-modified zinc oxide particles can be adjusted and mixed to be 1% by mass or more and 20% by mass or less. As required, the amount can also be 1% by mass or more and 10% by mass or less or 1% by mass or more and 5% by mass or less. The content of the silane coupling agent in the mixed solution can be, for example, 0.01% by mass or more and 11% by mass or less or 0.1% by mass or more and 10% by mass or less.

[0108] The amount of pure water can be arbitrarily selected, and is preferably appropriately adjusted to an amount required to promote the hydrolysis reaction of the silane coupling agent.

[0109] The amount of the catalyst can be arbitrarily selected, and is preferably appropriately adjusted to be an amount required to promote the hydrolysis reaction of the silane coupling agent. The catalyst can be an acid or a base.

[0110] Examples of the acid include inorganic acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, sulfuric acid, nitric acid, boric acid, and phosphoric acid, and organic acids such as acetic acid, citric acid, and formic acid. These acids may be used alone or in combination of two or more.

[0111] Examples of the base include sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, ammonia, amines, etc. These bases may be used alone or in combination of two or more.

[0112] "Disperser"

[0113] The disperser is not particularly limited as long as it can impart to the mixed liquid a dispersing energy of a degree that allows the zinc oxide particles to be surface treated while breaking up aggregation of the particles.

[0114] Examples of such a disperser include a colloid mill, a roll mill, an ultrasonic disperser, a high pressure homogenizer, an ultimizer, a rotary mill, a planetary mill, a bead mill, a sand mill, etc. As a dispersion medium used in a dispersion device using a dispersion medium, for example, granular bodies having a predetermined hardness, such as zirconium oxide, glass, aluminum oxide, titanium dioxide, and silicon nitride, can be used.

[0115] "Dispersed process"

[0116] In the dispersing step, the mixed solution is dispersed using a disperser at a predetermined energy or more to obtain surface-modified zinc oxide particles.

[0117] The energy given to the mixed solution can be appropriately adjusted according to the size of the dispersion machine. Therefore, the conditions for dispersion can be appropriately selected. For example, when utilizing a mill, for example, using a container with a capacity of about 1L and utilizing a bead mill for dispersion treatment, it is preferred to carry out dispersion treatment for more than 1 hour and less than 10 hours with a rotating speed of more than 500rpm. However, the conditions can be selected as needed and are not limited to the conditions.

[0118] Furthermore, when a mill is used, for example, a bead mill is used to perform dispersion treatment using a container having a capacity of about 1 L, the dispersion energy imparted to the mixed solution is preferably, for example, 100 W·h / kg or more and 600 W·h / kg or less. However, the conditions can be selected as needed and are not limited to the above conditions.

[0119] The crushing force of the bead mill depends on the centrifugal force of the beads on the outer periphery of the disk or pin in the mill. Therefore, it is preferable to calculate the product (impulse) of the centrifugal force and the dispersion time when the bead weight is the total weight of the beads in the mill to be 0.5×10 6 N·s or more and 100×10 6 Dispersion processing below N·s.

[0120] Furthermore, the surface modified zinc oxide particles can be dispersed to the * At this time, the b value of the zinc oxide particles can be measured by extracting a small amount of the zinc oxide particles in the dispersion treatment and using a spectrocolorimeter to measure the b value of the zinc oxide particles. * To confirm the degree of dispersion processing.

[0121] The temperature in the dispersion step is not particularly limited, but is preferably, for example, 20° C. or higher and 45° C. or lower.

[0122] In addition, the present invention includes: a step of placing a silane coupling agent having an alkoxy group, a solvent (dispersion medium) and zinc oxide particles into a disperser to prepare a mixed solution; and a step of dispersing the mixed solution using a disperser to obtain surface-modified zinc oxide particles having a d50 of 4 μm or less. In the step of preparing the mixed solution, the content of the solvent in the mixed solution can be adjusted to 40% by mass or more and 95% by mass or less to obtain the surface-modified zinc oxide particles of the present invention. Here, d50 represents a value measured by the following measurement method.

[0123] (Measurement method)

[0124] 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane, and 2 g of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane were mixed to obtain a mixed solution, and the obtained mixed solution was dispersed at 9500 rpm for 5 minutes using a homogenizer to obtain a dispersion solution. A measurement solution was prepared by diluting the obtained dispersion solution with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles in the obtained dispersion solution became 0.01% by mass. Using the obtained measurement solution, d50 was measured using a laser diffraction / scattering particle size distribution analyzer.

[0125] Here, as cyclopentasiloxane, DOWSIL SH245 Fluid manufactured by Dow Toray Industries, Ltd. can be used, and as polyglyceryl-3 polydimethylsilyl hydroxyethyl dimethicone, KF-6106 manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0126] The dispersion energy required to obtain the desired surface-modified zinc oxide particles varies depending on various conditions such as the type of dispersion device used and the filling amount, and therefore it is difficult to determine it uniquely.

[0127] Therefore, by measuring d50 of the obtained surface-modified zinc oxide particles by the above-mentioned measuring method, it can be confirmed whether the dispersion energy is sufficient.

[0128] Furthermore, in the present invention, the preferred surface-modified zinc oxide particles can also be selected by the following method. First, surface-modified zinc oxide particles having a silane coupling agent on the surface, the silane coupling agent having an alkoxy group, are prepared, and 10 g of the surface-modified zinc oxide particles, 88 g of cyclopentasiloxane, and 2 g of polyglycerol-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane are mixed to obtain a mixed solution. The obtained mixed solution is dispersed at 9500 rpm for 5 minutes using a homogenizer to obtain a dispersion solution, and a measurement solution is prepared in which the content of the surface-modified zinc oxide particles in the obtained dispersion solution is diluted with cyclopentasiloxane to 0.01 mass %. Using the obtained measurement solution, the particle size d50 when the cumulative volume percentage of the particle size distribution is 50% is measured using a laser diffraction / scattering particle size distribution measuring device to determine whether the d50 is 4 μm or less. When the d50 is 4 μm or less, the surface-modified zinc oxide particles can be selected as preferred surface-modified zinc oxide particles.

[0129] "Heating process"

[0130] From the viewpoint of accelerating the surface treatment step of the silane coupling agent, the heating step may be performed simultaneously with the dispersion step or after the dispersion step.

[0131] The heating temperature is not particularly limited as long as it is a temperature that promotes the surface treatment, and is preferably, for example, 40° C. to 150° C. If necessary, it may be 40° C. to 80° C. or 60 to 100° C.

[0132] "Drying process"

[0133] The liquid after the dispersion treatment is preferably dried using a drying device. In addition, solid-liquid separation and other treatments to shorten the drying time may be performed before drying. The drying device is not particularly limited, and examples thereof include a box dryer, a vacuum dryer, a vibration dryer, a fluidized bed dryer, a belt dryer, an evaporator, a Nauta mixer, a Henschel mixer, a RIBOCONE, a paddle dryer, a spray dryer, a slurry dryer, a flash dryer, a rotary dryer, and the like.

[0134] The drying temperature is not particularly limited as long as it is a temperature at which the solvent can be removed, and is preferably, for example, 50° C. to 200° C., and may be 60° C. to 150° C. or 70° C. to 120° C., etc.

[0135] Crushing process

[0136] The dried surface-modified zinc oxide particles can be crushed using a crusher. Any crusher can be selected, for example, an atomizer, a hammer mill, a jet mill, an impeller mill, a pin mill, etc. The crushing process can suppress the roughness of the surface-modified zinc oxide particles when mixed into cosmetics. That is, the feeling of use when the surface-modified zinc oxide particles are used in cosmetics can be improved.

[0137] [Dispersion liquid]

[0138] The dispersion liquid of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment and a dispersion medium. The dispersion liquid can be formed by preparing the surface-modified zinc oxide particles of the present embodiment and mixing them with the dispersion medium.

[0139] In addition, the dispersion liquid of the present embodiment can also preferably contain a paste-like dispersion having a high viscosity.

[0140] The dispersion medium is not particularly limited as long as it can disperse the surface-modified zinc oxide particles. When the surface-modified zinc oxide particles are used as cosmetics, the dispersion medium is not particularly limited as long as it can be formulated into cosmetics.

[0141] Examples of the dispersion medium include chain polysiloxanes such as dimethylpolysiloxane, methylphenylpolysiloxane, and diphenylpolysiloxane, cyclic polysiloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane, amino-modified polysiloxane, polyether-modified polysiloxane, alkyl-modified polysiloxane, and modified polysiloxanes such as fluorine-modified polysiloxane, liquid paraffin, squalane, isoparaffin, branched light paraffin, vaseline, and diatomaceous earth. Hydrophobic dispersion media including wax, dodecane, isododecane, tridecane, tetradecane, hexadecane, isohexadecane, octadecane and other hydrocarbon oils; ester oils including isopropyl myristate, hexadecyl isooctanoate, tricaprylin, tri(caprylic / capric)glyceryl, alkyl benzoate (C12-15) and other ester oils; higher fatty acids including lauric acid, myristic acid, palmitic acid, stearic acid and other higher alcohols including lauryl alcohol, cetyl alcohol, stearyl alcohol, octyldodecanol, isostearyl alcohol and other hydrophobic dispersion media. In addition, there can be mentioned alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, octanol, glycerol, etc.; esters such as ethyl acetate, butyl acetate, ethyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, γ-butyrolactone, etc.; ethers such as ethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, etc.; benzene, toluene, ethylbenzene, Aromatic hydrocarbons such as 1-phenylpropane, isopropylbenzene, n-butylbenzene, tert-butylbenzene, sec-butylbenzene, o-, m- or p-xylene, 2-, 3- or 4-ethyltoluene; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone; amides such as dimethylformamide, N,N-dimethylacetoacetamide, N-methylpyrrolidone; nitriles such as acetonitrile; natural oils such as oleic acid, jojoba oil, olive oil, coconut oil, grape seed oil, castor oil, rice bran oil, horse oil, mink oil, etc.

[0142] These dispersion media may be used alone or in combination of two or more.

[0143] When the surface-modified zinc oxide particles are used for cosmetic purposes, the dispersion medium preferably uses the above-mentioned linear polysiloxane, the above-mentioned cyclic polysiloxane, the above-mentioned modified polysiloxane, the above-mentioned hydrocarbon oil, the above-mentioned ester oil, the above-mentioned higher fatty acid, the above-mentioned higher alcohol, the above-mentioned natural oil, ethanol, glycerol, etc.

[0144] These dispersion media may be used alone or in combination of two or more.

[0145] The dispersion liquid of the present embodiment may contain commonly used additives within a range that does not impair its characteristics.

[0146] Examples of the additive include preservatives, dispersants, dispersing aids, stabilizers, water-soluble binders, thickeners, oil-soluble drugs, oil-soluble pigments, oil-soluble proteins, and UV absorbers.

[0147] The particle size (d50) at which the cumulative volume percentage of the particle size distribution in the dispersion of this embodiment is 50% can be arbitrarily selected, but is preferably 300 nm or less (0.3 μm or less), more preferably 250 nm or less, and further preferably 200 nm or less. It may also be 150 nm or less or 100 nm or less.

[0148] The lower limit of d50 is not particularly limited, and may be, for example, 20 nm or more, 40 nm or more, or 60 nm or more.

[0149] The upper limit value and the lower limit value of d50 can be arbitrarily combined.

[0150] Furthermore, the particle size (d90) when the cumulative volume percentage of the particle size distribution in the dispersion of the present embodiment is 90% is preferably 350 nm or less, more preferably 300 nm or less, and even more preferably 250 nm or less.

[0151] The lower limit of d90 is not particularly limited, and may be, for example, 60 nm or more, 80 nm or more, or 100 nm or more.

[0152] The upper limit value and the lower limit value of d90 can be combined arbitrarily.

[0153] When the d50 of the dispersion is 300 nm or less, when the cosmetic prepared using the dispersion is applied to the skin, the surface-modified zinc oxide particles are easily evenly distributed, thereby improving the ultraviolet shielding effect, which is preferred. In addition, when the d90 of the dispersion is 350 nm or less, the transparency of the dispersion is high, and the transparency of the cosmetic prepared using the dispersion is also high, which is preferred.

[0154] That is, when d50 and d90 in the dispersion of the present embodiment are within the above ranges, a dispersion having excellent transparency and excellent ultraviolet shielding properties can be obtained. Furthermore, a cosmetic prepared using the dispersion also has excellent transparency and ultraviolet shielding properties.

[0155] As a method for measuring the cumulative volume percentage of the particle size distribution in the dispersion liquid of the present embodiment, for example, there is a method using a dynamic light scattering particle size distribution measuring apparatus (model: LB-550, manufactured by Horiba, Ltd.).

[0156] The content of the surface-modified zinc oxide particles in the dispersion of the present embodiment can be appropriately adjusted according to the properties of the target dispersion.

[0157] When the dispersion of the present embodiment is used in a cosmetic, the content of the surface-modified zinc oxide particles in the dispersion is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. Furthermore, the content of the surface-modified zinc oxide particles in the dispersion is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.

[0158] The upper limit and lower limit of the content of the surface-modified zinc oxide particles in the dispersion may be arbitrarily combined.

[0159] When the content of the surface-modified zinc oxide particles in the dispersion is within the above range, the dispersion can contain a high concentration of surface-modified zinc oxide particles, thereby increasing the degree of freedom in formulating cosmetics produced using the dispersion and adjusting the viscosity of the dispersion within a range that is easy to handle.

[0160] The method for producing the dispersion liquid of the present embodiment is not particularly limited, and for example, a method of mechanically dispersing the surface-modified zinc oxide particles of the present embodiment and a dispersion medium using a known dispersing device can be mentioned.

[0161] The dispersing device can be selected as needed. Examples of the dispersing device include a stirrer, a rotation-revolution mixer, a homomixer, an ultrasonic homogenizer, a sand mill, a ball mill, and a roll mill.

[0162] In addition to cosmetics, the dispersion liquid of the present embodiment can be used for coating materials having an ultraviolet shielding function, a gas permeation suppressing function, and the like.

[0163] According to the dispersion of the present embodiment, since the surface-modified zinc oxide particles of the present embodiment are contained, the production efficiency of the dispersion is good and high ultraviolet shielding properties are stably exhibited.

[0164] [Composition]

[0165] The composition of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment, a resin, and a dispersion medium. The composition can be prepared by preparing the surface-modified zinc oxide particles of the present embodiment and mixing the resin and the dispersion medium.

[0166] The content of the surface-modified zinc oxide particles in the composition of this embodiment can be appropriately adjusted according to the properties of the target composition. The content of the surface-modified zinc oxide particles in the composition of this embodiment is, for example, preferably 10% by mass or more and 40% by mass or less, and more preferably 20% by mass or more and 30% by mass or less.

[0167] When the content of the surface-modified zinc oxide particles in the composition is within the above range, the composition can contain a high concentration of the surface-modified zinc oxide particles. Therefore, the properties of the surface-modified zinc oxide particles can be fully obtained, and a composition in which the surface-modified zinc oxide particles are uniformly dispersed can be obtained.

[0168] The dispersion medium is not particularly limited as long as it is a dispersion medium generally used in industrial applications. Examples of the dispersion medium include alcohols such as methanol, ethanol, and propanol, methyl acetate, ethyl acetate, toluene, methyl ethyl ketone, and methyl isobutyl ketone.

[0169] The content of the dispersion medium in the composition of the present embodiment is not particularly limited and can be appropriately adjusted according to the properties of the target composition.

[0170] The resin is not particularly limited as long as it is a resin generally used for industrial purposes. Examples of the resin include acrylic resins, epoxy resins, urethane resins, polyester resins, and silicone resins.

[0171] The content of the resin in the composition of the present embodiment is not particularly limited and can be appropriately adjusted according to the properties of the target composition.

[0172] The composition of the present embodiment may contain commonly used additives within a range that does not impair the properties thereof.

[0173] Examples of the additive include a polymerization initiator, a dispersant, and an antiseptic.

[0174] The method for producing the composition of the present embodiment is not particularly limited, and an example thereof includes a method of mechanically mixing the surface-modified zinc oxide particles of the present embodiment, a resin, and a dispersion medium using a known mixing device.

[0175] Furthermore, there can be mentioned a method of mechanically mixing the dispersion and the resin using a known mixing device.

[0176] Examples of the mixing device include a stirrer, a rotation-revolution mixer, a homomixer, and an ultrasonic homogenizer.

[0177] The composition of this embodiment can be applied to a plastic substrate such as a polyester film by a common coating method such as roll coating, flow coating, spray coating, screen printing, brush coating, dipping, etc. to form a coating film. These coating films can be used as ultraviolet shielding films or gas barrier films.

[0178] According to the composition of the present embodiment, since the surface-modified zinc oxide particles of the present embodiment are contained, the production efficiency of the composition is good and high ultraviolet shielding properties are stably exhibited.

[0179] [Cosmetics]

[0180] The cosmetic of the present embodiment contains at least one of the surface-modified zinc oxide particles of the present embodiment and the dispersion of the present embodiment, and a cosmetic base raw material.

[0181] Here, the cosmetic base raw materials refer to various raw materials that form the main body of cosmetics, and examples thereof include oily raw materials, water-based raw materials, surfactants, powder raw materials, and the like.

[0182] Examples of the oily raw material include fats and oils, higher fatty acids, higher alcohols, and ester oils.

[0183] Examples of the aqueous raw material include purified water, alcohol, and a thickener.

[0184] Examples of the powder raw material include color pigments, white pigments, pearlescent agents, and extender pigments.

[0185] In the present embodiment, the raw material of the cosmetic base may preferably be an oily raw material, a powdery raw material, or an oily raw material and a powdery raw material, and an oily raw material may more preferably be used.

[0186] The cosmetics of this embodiment may refer to oily cosmetics, emulsion-type cosmetics containing surface-modified zinc oxide particles in an oil phase, powdered solid cosmetics formed by mixing surface-modified zinc oxide particles with an oil agent and then removing the oil agent, and the like, which are cosmetics containing surface-modified zinc oxide particles in the oil component (oil phase) during the manufacturing process or in the final form.

[0187] The emulsion-type cosmetic may be an O / W emulsion or a W / O emulsion.

[0188] In other words, the cosmetic of the present embodiment preferably contains at least one of the surface-modified zinc oxide particles of the present embodiment and the dispersion of the present embodiment in the oil component or the oil phase.

[0189] The oil component used in the oil phase of an oily cosmetic or emulsion is not particularly limited as long as it is an oil component commonly used in cosmetics, and examples thereof include silicone oil, fats and oils, higher fatty acids, higher alcohols, ester oils, and natural oils.

[0190] Furthermore, the cosmetic of the present embodiment may contain the aqueous raw material, surfactant, powder raw material, etc. as long as the properties thereof are not impaired.

[0191] The cosmetic of the present embodiment is obtained, for example, by blending the surface modified zinc oxide particles or dispersion of the present embodiment into a base of cosmetics such as lotion, cream, sunscreen, foundation, lipstick, blush, eye shadow, etc. in the same manner as conventionally.

[0192] The cosmetic of the present embodiment is obtained by blending the surface-modified zinc oxide particles of the present embodiment into an oil phase to form an O / W type or W / O type emulsion, and blending the emulsion with the raw materials of the cosmetic.

[0193] The content of the surface-modified zinc oxide particles in the cosmetic of the present embodiment can be appropriately adjusted according to the characteristics of the target cosmetic. For example, the lower limit of the content of the surface-modified zinc oxide particles can be 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more. In addition, the upper limit of the content of the surface-modified zinc oxide particles can be 50% by mass or less, 40% by mass or less, or 30% by mass or less.

[0194] The upper limit and lower limit of the content of the surface-modified zinc oxide particles in the cosmetic may be arbitrarily combined.

[0195] Hereinafter, sunscreen cosmetics will be specifically described as an example of cosmetics.

[0196] In order to effectively shield ultraviolet rays (especially long-wavelength ultraviolet rays (UVA)) and obtain a good feeling of use with less powdery or astringent feeling, the lower limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and further preferably 1% by mass or more. In addition, the upper limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic can be 50% by mass or less, 40% by mass or less, or 30% by mass or less. The upper limit and lower limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic can be arbitrarily combined.

[0197] Sunscreen cosmetics may contain hydrophobic dispersion medium, inorganic fine particles or inorganic pigments other than surface-modified zinc oxide particles, hydrophilic dispersion medium, oil, surfactant, moisturizer, thickener, pH adjuster, nutrient, antioxidant, fragrance, etc. as needed.

[0198] Examples of the hydrophobic dispersion medium include hydrocarbon oils such as liquid paraffin, squalane, isoparaffin, branched light paraffin, vaseline, and ozokerite; ester oils such as isopropyl myristate, cetyl isooctanoate, and tricaprylin; silicone oils such as decamethylcyclopentasiloxane, dimethylpolysiloxane, and methylphenylpolysiloxane; higher fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid; and higher alcohols such as lauryl alcohol, cetyl alcohol, stearyl alcohol, hexyldodecanol, and isostearyl alcohol.

[0199] Examples of inorganic fine particles or inorganic pigments other than the surface-modified zinc oxide particles contained in cosmetics include calcium carbonate, calcium phosphate (apatite), magnesium carbonate, calcium silicate, magnesium silicate, aluminum silicate, kaolin, talc, titanium oxide, aluminum oxide, yellow iron oxide, γ-iron oxide, cobalt titanate, cobalt violet, silicon oxide, and the like.

[0200] Sunscreen cosmetics may further contain at least one organic ultraviolet light absorber.

[0201] Examples of the organic ultraviolet absorber include benzotriazole ultraviolet absorbers, benzoylmethane ultraviolet absorbers, benzoic acid ultraviolet absorbers, anthranilic acid ultraviolet absorbers, salicylic acid ultraviolet absorbers, cinnamic acid ultraviolet absorbers, and silicone cinnamic acid ultraviolet absorbers.

[0202] Examples of the benzotriazole-based ultraviolet absorber include 2,2′-hydroxy-5-methylphenylbenzotriazole, 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole, and 2-(2′-hydroxy-5′-methylphenyl)benzotriazole.

[0203] Examples of the benzoylmethane ultraviolet absorber include dibenzalazine, anisyl methane, 4-tert-butyl-4′-methoxydibenzoylmethane, 1-(4′-isopropylphenyl)-3-phenylpropane-1,3-dione, and 5-(3,3′-dimethyl-2-norbornylidene)-3-pentan-2-one.

[0204] Examples of the benzoic acid-based ultraviolet absorber include para-aminobenzoic acid (PABA), PABA monoglyceride, N,N-dipropoxy PABA ethyl ester, N,N-diethoxy PABA ethyl ester, N,N-dimethyl PABA ethyl ester, N,N-dimethyl PABA butyl ester, and N,N-dimethyl PABA methyl ester.

[0205] Examples of the anthranilic acid-based ultraviolet absorber include homomenium N-acetylanthranilate.

[0206] Examples of the salicylic acid-based ultraviolet absorber include amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, and p-2-propanolphenyl salicylate.

[0207] Examples of the cinnamic acid-based ultraviolet absorber include octyl methoxycinnamate (ethylhexyl methoxycinnamate), di-p-methoxycinnamic acid-mono-2-ethylhexanoic acid glyceryl ester, octyl cinnamate, ethyl 4-isopropylcinnamate, methyl 2,5-diisopropylcinnamate, ethyl 2,4-diisopropylcinnamate, methyl 2,4-diisopropylcinnamate, propyl p-methoxycinnamate, isopropyl p-methoxycinnamate, isoamyl p-methoxycinnamate, octyl p-methoxycinnamate (2-ethylhexyl p-methoxycinnamate), 2-ethoxyethyl p-methoxycinnamate, cyclohexyl p-methoxycinnamate, ethyl α-cyano-β-phenylcinnamate, 2-ethylhexyl α-cyano-β-phenylcinnamate, and glyceryl mono-2-ethylhexanoyl-di-p-methoxycinnamate.

[0208] Examples of the silicone cinnamic acid ultraviolet absorber include [3-bis(trimethylsilyloxy)methylsilyl-1-methylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsilyloxy)methylsilyl-3-methylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsilyloxy)methylsilylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsilyloxy)methylsilylbutyl]-3,4,5-trimethoxycinnamate, [3-tris(trimethylsilyloxy)silylbutyl]-3,4,5-trimethoxycinnamate, and [3-tris(trimethylsilyloxy)silyl-1-methylpropyl]-3,4-dimethoxycinnamate.

[0209] Examples of organic ultraviolet absorbers other than the above include 3-(4'-methylbenzylidene)-d,l-camphor, 3-benzylidene-d,l-camphor, urocannic acid, ethyl urocannic acid, 2-phenyl-5-methylbenzoxazole, 5-(3,3'-dimethyl-2-nitrobornyl)-3-pentan-2-one, silicone-modified ultraviolet absorbers, and fluorine-modified ultraviolet absorbers.

[0210] According to the cosmetic of the present embodiment, since the surface-modified zinc oxide particles of the present embodiment are contained, the cosmetic can be easily dispersed in an oil component, so the production efficiency is good, and a high ultraviolet shielding property is stably exhibited.

[0211] Example

[0212] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0213] [Example 1]

[0214] "Preparation of surface-modified zinc oxide particles"

[0215] The mixed surface area is 21.3m 2 / g,b * 33.3 parts by mass of 3.33 zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.), 2.0 parts by mass of octyltriethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-3083), 0.4 parts by mass of pure water, and 64.3 parts by mass of isopropyl alcohol.

[0216] Next, the mixed solution was dispersed for 3 hours using a bead mill. The dispersion conditions were a rotation speed of 2500 rpm and a temperature of 20°C.

[0217] The dispersion liquid from which the beads were removed was subjected to solid-liquid separation and dried at 80° C. for 2 hours to obtain the surface-modified zinc oxide particles of Example 1.

[0218] The specific surface area of ​​the surface-modified zinc oxide particles of Example 1 was measured using a fully automatic specific surface area measuring device (trade name: Macsorb HM Model-1201, manufactured by MOUNTECH Corporation).

[0219] In addition, the d50 and b of the particles were measured by the following method: * .

[0220] "Surface modified zinc oxide particles * Determination of

[0221] The b value of the surface-modified zinc oxide particles of Example 1 was measured using a spectrocolorimeter (Spectro Color Meter SE7700 manufactured by Nippon Denshoku Industries Co., Ltd.). * The light source is D65, and the reflection (light 2 degree field of view) measurement condition is The diameter was measured.

[0222] Regarding the measurement sample, 10 g of the surface-modified zinc oxide particles of Example 1 were placed in a 30 mL spiral tube, which was tapped 30 times on a table, and the bottom surface of the spiral tube was used as the measurement surface.

[0223] "Preparation of dispersion liquid"

[0224] 10 g of the surface-modified zinc oxide particles of Example 1, 88 g of cyclopentasiloxane (manufactured by Dow Toray Industries, Inc., model: DOWSIL SH245 Fluid), and 2 g of polyglyceryl-3 polydimethylsilyl hydroxyethyl dimethicone (manufactured by Shin-Etsu Chemical Co., Ltd., model: KF-6106) were mixed to obtain a mixed solution.

[0225] Next, the mixed solution was dispersed using a homogenizer (manufactured by IKA Corporation, ULTRA-TURRAX (registered trademark) series: T25 basic) at 9500 rpm for 5 minutes to obtain a dispersion of Example 1.

[0226] "Evaluation of dispersibility based on particle size distribution"

[0227] The dispersion liquid of Example 1 was diluted with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles became 0.01 mass %, thereby preparing a measurement liquid.

[0228] Using this measurement liquid, d50 was measured using a laser diffraction / scattering particle size distribution analyzer (manufactured by Horiba, Ltd., model: LA-920).

[0229] In addition, the particle size (d10) when the cumulative volume percentage of the particle size distribution is 10% and the particle size (d90) when the cumulative volume percentage of the particle size distribution is 90% were measured in the same manner as d50. The results are shown in Table 1.

[0230] "Evaluation of the transparency of dispersion liquid"

[0231] The dispersion of Example 1 was diluted with cyclopentasiloxane so that the concentration of the surface-modified zinc oxide particles became 0.005 mass %.

[0232] The linear transmittance T1 (%) at 360 nm and 550 nm and the total transmittance T2 (%) at 360 nm and 550 nm of the diluted solution were measured using an ultraviolet-visible-near-infrared spectrophotometer (manufactured by JASCO Corporation, model: V-770).

[0233] A low transmittance at 360 nm indicates high ultraviolet shielding properties. Therefore, a low transmittance at 360 nm is preferred.

[0234] A high transmittance at 550 nm indicates high transparency. Therefore, a high transmittance at 550 nm is preferred.

[0235] [Example 2]

[0236] In Example 1, a specific surface area of ​​24.2 m 2 / g,b * Instead of using zinc oxide particles with a specific surface area of ​​21.3 m 2 / g,b * Surface-modified zinc oxide particles of Example 2 were obtained in the same manner as in Example 1 except that the zinc oxide particles had a g / cm3 of 3.33.

[0237] The specific surface area and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0238] The dispersion of Example 2 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 2 were used instead of the surface-modified zinc oxide particles of Example 1.

[0239] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0240] [Example 3]

[0241] In Example 1, a specific surface area of ​​38.2 m 2 / g,b * Instead of using zinc oxide particles with a specific surface area of ​​21.3 m2 / g,b * Surface-modified zinc oxide particles of Example 3 were obtained in the same manner as in Example 1 except that the zinc oxide particles had a g / cm3 of 3.33.

[0242] The specific surface area and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0243] A dispersion of Example 3 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 3 were used instead of the surface-modified zinc oxide particles of Example 1.

[0244] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0245] [Example 4]

[0246] Surface-modified zinc oxide particles of Example 4 were obtained in the same manner as in Example 3 except that the dispersion treatment was performed for 9 hours instead of for 3 hours.

[0247] The product of the centrifugal force and the dispersion time during dispersion (impulse) was about 3 times that of Example 1. The specific surface area and b * The results are shown in Table 1.

[0248] A dispersion of Example 4 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 4 were used instead of the surface-modified zinc oxide particles of Example 1.

[0249] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0250] [Comparative Example 1]

[0251] In Example 3, the surface-modified zinc oxide particles of Comparative Example 1 were obtained in the same manner as in Example 3 except that the dispersion treatment was performed for 5 minutes instead of for 3 hours.

[0252] The product of the centrifugal force and the dispersion time during dispersion (impulse) was about 1 / 40 of that in Example 1. The specific surface area and b * The results are shown in Table 1.

[0253] A dispersion of Comparative Example 1 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Comparative Example 1 were used instead of the surface-modified zinc oxide particles of Example 1.

[0254] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0255] [Comparative Example 2]

[0256] The specific surface area is 38.2m 2 / g,b * 100 parts by mass of zinc oxide particles with a viscosity of 3.42 were put into a Henschel mixer. While the zinc oxide particles were stirred by the Henschel mixer, a mixed solution of 5 parts by mass of octyltriethoxysilane (trade name: KBE-3083, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.375 parts by mass of pure water, and 7.125 parts by mass of isopropyl alcohol was added. The mixture was mixed in the Henschel mixer and stirred for 1 hour.

[0257] Next, the obtained mixture was pulverized by a jet mill, and the pulverized powder was dried at 100° C., thereby obtaining surface-modified zinc oxide particles of Comparative Example 2.

[0258] The specific surface area and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0259] A dispersion liquid of Comparative Example 2 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Comparative Example 2 were used instead of the surface-modified zinc oxide particles of Example 1.

[0260] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0261] [Table 1]

[0262]

[0263] The results in Table 1 show that the surface-modified zinc oxide particles of Examples 1 to 4 have smaller d50 and are excellent in ultraviolet shielding properties than the surface-modified zinc oxide particles of Comparative Examples 1 and 2, and have transparency equal to or higher than that of the surface-modified zinc oxide particles of Comparative Examples 1 and 2.

[0264] [Example 5]

[0265] In Example 1, a specific surface area of ​​5.1 m 2 / g,b * Instead of using zinc oxide particles with a specific surface area of ​​21.3 m 2 / g,b * Surface-modified zinc oxide particles of Example 5 were obtained in the same manner as in Example 1 except that the zinc oxide particles had a g / cm3 of 3.33.

[0266] The specific surface area and b were measured in the same manner as in Example 1. * The results are shown in Table 2.

[0267] A dispersion of Example 5 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 5 were used instead of the surface-modified zinc oxide particles of Example 1.

[0268] d10, d50, and d90 were measured in the same manner as in Example 1. Table 2 shows the results.

[0269] [Example 6]

[0270] In Example 1, a specific surface area of ​​7.4 m 2 / g,b * Instead of using zinc oxide particles with a specific surface area of ​​21.3 m 2 / g,b * Surface-modified zinc oxide particles of Example 6 were obtained in the same manner as in Example 1 except that the zinc oxide particles had a g / cm3 of 3.33.

[0271] The specific surface area and b were measured in the same manner as in Example 1. * The results are shown in Table 2.

[0272] A dispersion of Example 6 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 6 were used instead of the surface-modified zinc oxide particles of Example 1.

[0273] d10, d50, and d90 were measured in the same manner as in Example 1. Table 2 shows the results.

[0274] [Comparative Example 3]

[0275] In Example 5, the surface-modified zinc oxide particles of Comparative Example 3 were obtained in the same manner as in Example 5, except that the dispersion treatment was performed for 5 minutes instead of for 3 hours.

[0276] The product of the centrifugal force and the dispersion time during dispersion (impulse) was about 1 / 40 of that in Example 1. The specific surface area and b * The results are shown in Table 2.

[0277] A dispersion of Comparative Example 3 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Comparative Example 3 were used instead of the surface-modified zinc oxide particles of Example 1.

[0278] d10, d50, and d90 were measured in the same manner as in Example 1. Table 2 shows the results.

[0279] [Table 2]

[0280]

[0281] It was confirmed that the surface-modified zinc oxide particles of Examples 5 and 6 had smaller d50 than the surface-modified zinc oxide particles of Comparative Example 3. It was also confirmed that the surface-modified zinc oxide particles of Examples 5 and 6 had superior ultraviolet shielding properties compared to Comparative Example 3 and had transparency equal to or higher than that of Comparative Example 3.

[0282] “Evaluation of dispersibility”

[0283] 1 g of the surface-modified zinc oxide particles of Examples 1 to 6 and Comparative Examples 1 to 3 were each slowly added to a spiral tube containing 20 g of cyclopentasiloxane, and the condition of the spiral tube was observed after 20 minutes.

[0284] As a result, it was confirmed that the surface-modified zinc oxide particles of Examples 1 to 6 were dispersed as a whole, whereas a large number of particles were precipitated in the surface-modified zinc oxide particles of Comparative Examples 1 to 3. The results of Example 4 and Comparative Example 2 are shown in FIG. Figure 1 . Figure 1 The spiral tube on the right side of contains the surface-modified zinc oxide particles obtained in Example 4. Figure 1 The spiral tube on the left side of contains the surface-modified zinc oxide particles obtained in Comparative Example 2. Figure 1 As shown, in Example 4, it was confirmed that the entire surface-modified zinc oxide particles were dispersed. On the other hand, in Comparative Example 2, it was confirmed that a large amount of surface-modified zinc oxide particles were precipitated.

[0285] That is, it was found that the surface-modified zinc oxide particles of Examples 1 to 6 whose dispersions prepared under predetermined conditions had d50 of 4 μm or less were easily dispersed in the dispersion medium even when the dispersion energy was small during the preparation of the cosmetic.

[0286] Industrial Applicability

[0287] The present invention can provide a surface-modified zinc oxide particle which is easy to be blended into an oily cosmetic and has excellent transparency and ultraviolet shielding properties. The surface-modified zinc oxide particle of the present invention has excellent dispersibility and thus excellent ultraviolet shielding properties, and also has a transparency equal to or higher than that of conventional particles, and therefore has great industrial value when used in cosmetics.

Claims

1. A surface-modified zinc oxide particle having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group, wherein the surface-modified zinc oxide particle is characterized in that: The particle size distribution measured by the following measurement method using a laser diffraction / scattering particle size distribution measuring device has a particle size d50 of 4 μm or less when the cumulative volume percentage is 50%. The determination method is as follows: 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane, and 2 g of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane were mixed to obtain a mixed solution 1. The obtained mixed solution 1 was dispersed using a homogenizer at 9500 rpm for 5 minutes to obtain a dispersion. A measurement solution was prepared by diluting the dispersion with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles in the dispersion obtained was 0.01 mass %. Using the obtained measurement liquid, d50 was measured using a laser diffraction / scattering particle size distribution analyzer.

2. The surface-modified zinc oxide particles according to claim 1, characterized in that b* in the L*a*b* color system chromaticity diagram is 4.0 or more and 18 or less.

3. The surface-modified zinc oxide particles according to claim 1 or 2, characterized in that The silane coupling agent is at least one selected from the group consisting of alkylalkoxysilane, allylalkoxysilane, polysiloxane having an alkyl group at a side chain, and polysiloxane having an allyl group at a side chain.

4. The surface-modified zinc oxide particles according to claim 1 or 2, characterized in that The silane coupling agent is at least one selected from the group consisting of octyltriethoxysilane, octyltrimethoxysilane, and dimethoxydiphenylsilane-triethoxyoctanoylsilane cross-linked polymer.

5. The surface-modified zinc oxide particles according to claim 1 or 2, characterized in that Obtained as follows: A mixed solution 2 containing 1 mass % to 55 mass % of zinc oxide particles, 40 mass % to 95 mass % of a solvent, and a silane coupling agent having an alkoxy group is prepared. The mixed solution 2 is subjected to a dispersion treatment until the b* of the surface-modified zinc oxide particles becomes 4.0 or more and 18 or less, and then dried.

6. The surface-modified zinc oxide particles according to claim 5, wherein The mixed solution 2 also contains water and a catalyst.

7. A dispersion, characterized in that: The method comprises the surface-modified zinc oxide particles according to any one of claims 1 to 4 and a dispersion medium.

8. A cosmetic material, characterized in that: The invention comprises the surface-modified zinc oxide particles according to any one of claims 1 to 4 and a raw material for a cosmetic base.

9. A method for selecting surface-modified zinc oxide particles, which is the method for selecting surface-modified zinc oxide particles according to claim 1, wherein: Surface-modified zinc oxide particles having a silane coupling agent on the surface are prepared, wherein the silane coupling agent has an alkoxy group. 10 g of the surface-modified zinc oxide particles, 88 g of cyclopentasiloxane and 2 g of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane were mixed to obtain a mixed solution. The obtained mixed solution was dispersed using a homogenizer at 9500 rpm for 5 minutes to obtain a dispersion. A measurement solution was prepared in which the content of the surface-modified zinc oxide particles in the obtained dispersion was 0.01 mass % by dilution with cyclopentasiloxane. The obtained measurement solution was used to measure the particle size d50 when the cumulative volume percentage of the particle size distribution was 50% using a laser diffraction / scattering particle size distribution measuring device. Determine whether the d50 is 4 μm or less, When the d50 is 4 μm or less, the surface-modified zinc oxide particles are selected.

10. A method for producing surface-modified zinc oxide particles, which is the method for producing surface-modified zinc oxide particles according to claim 1, characterized in that: include: A step of placing a silane coupling agent having an alkoxy group, a solvent, and zinc oxide particles into a disperser to prepare a mixed solution; and The mixed solution is dispersed by a disperser to obtain surface-modified zinc oxide particles having a d50 of 4 μm or less. In the step of preparing the mixed liquid, the content of the solvent in the mixed liquid is 40 mass % or more and 95 mass % or less, and the dispersion energy applied to the mixed liquid is 100 W·h / kg or more.

Citation Information

Patent Citations

  • Zinc oxide powder and its synthesis

    JP2000095519A

  • Method for producing fine powder of zinc oxide, fine powder of zinc oxide and resin composition containing it

    JP2002284527A

  • Low smell alkylsilylated powder, method for producing the same, silicone oil slurry dispersed with the low smell alkylsilylated powder, and cosmetic mixed with the low smell alkylsilylated powder or the silicone oil slurry

    JP2007051188A

  • Surface-treated zinc oxide particles, dispersion liquid, cosmetic, and zinc oxide particles

    WO2017130632A1

  • Method for producing surface-treated zinc oxide particle

    WO2019026907A1